Two Early Ming Texts on Borneo. (March 2015) - Kurz, Johannes L.
Abstract : The present article provides translations of two texts from the early Ming dynasty. The first text describes a diplomatic mission from the Ming court to a place in Boni, most likely Borneo, in 1370 that was based on the report of the envoy and compiled by Song Lian. The second text, a tomb inscription, is the earliest record of the voyage of a chieftain from Boni to the Ming court in 1408, and his death and burial there within a month after his arrival. The significance of the texts consists in their being used nowadays as early evidence for the existence of a Muslim Malay Monarchy that lasts until today in the form of the sultanate of Brunei. In contrast, the two texts when read together do not support this view.